Unleashing The Power of Instruction: Internalizing Religious Moderation Values in Students’ EFL Writing - Nurul Puspita; Aryanika, Septa (Universitas Ahmad Dahlan, 2025)
Writing in English as a Foreign Language (EFL) is a special chance for students to improve their language skills and develop their social awareness. Through the use of writing prompts that promote values like tolerance, respect for others, and critical thinking, students are able to express themselves more effectively in English and gain a deeper comprehension of other viewpoints. This study used qualitative research to examine the effects of implementing religious moderation values on EFL students' writing ability. Analysis of the effects of exposure to these values on writing coherence, argumentation, and intercultural sensitivity was done using data acquired through students interviews and observation sheets. The results show that the incorporating of religious moderation in EFL lessons has a positive effect on students' language learning and knowledge of global cultural issues encouraging more considerate and polite conversation. The research emphasizes how learning a language together with a values-based education can result in students who are more adept and socially conscientious, especially in writing class.